Impact of Household Cooking Techniques on African Nightshade and Chinese Cabbage on Phenolic Compounds, Antinutrients, in vitro Antioxidant, and β-Glucosidase Activity - Managa, Millicent G.; Shai, Jerry; Thi Phan, Anh Dao; Sultanbawa, Yasmina; Sivakumar, Dharini (Frontiers in Nutrition, 2020)
Different household cooking techniques (boiling, steaming, stir frying, and microwave) were tested on the changes of targeted phenolic compounds, antioxidant property (ferric reducing-antioxidant power (FRAP) activity), α-glucosidase activity, antinutritive compounds, and sensory properties in commonly consumed traditional leafy vegetables in Southern Africa, the non-heading Chinese cabbage (Brassica rapa L. subsp. chinensis) and African nightshade (Solanum retroflexum Dun). Stir frying increased kaempferol-3-O-hydroxyferuloyl-trihexoside, kaempferol-dihexoside, sinapoyl malate, rutin, and isorhamnetin-O-dihexoside in Chinese cabbage leaves, followed by steaming. Similarly, stir frying increased kaempferol-3-O-rutinoside, chlorogenic acid, caffeoylmalic acid, and quercetin-3-O-xylosyl-rutinoside in nightshade, followed by steaming. Biomarkers, sinapoyl malate (Chinese cabbage) and caffeoylmalic acid (nightshade), separated the stir frying from the other cooking techniques. Steaming and stir-frying techniques significantly increased the FRAP activity; whereas boiling and microwaving reduced the tannin, oxalate, and phytate contents in both leafy vegetables and steroidal saponins in nightshade. Stir-fried nightshade leaf extract showed the most effective inhibition against α-glucosidase activity, with an IC50 of 26.4 μg ml−1, which was higher than acarbose, a synthetic compound (positive control; IC50 69.83 μg ml−1). Sensory panelists preferred the stir-fried Chinese cabbage and nightshade leaves, followed by steamed, microwaved, and boiled vegetables.